INTERNATIONAL CONFERENCE ON ADVANCES IN BIOSCIENCES AND BIOTECHNOLOGY- 2021 - GARIMA MATHUR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Clustered Regularly Interspaced Short Palindromic Repeats, or CRISPR is the adaptive immune system of prokaryotes that retains protospacer of phages and plasmids from past infections, as spacers flanked between palindromic repeats in a CRISPR array. The crRNA binds with tracrRNA and Cas9 protein to form gRNA which binds with the complementary protospacer of the viral DNA. Cas9 protein, an endonuclease, then chops off the viral DNA 3 base pairs before PAM leading to disintegration of the viral genome, thereby preventing infections. This technology has gained widespread attention amongst scientists and researchers due to its versatility, accuracy, and simplicity of utilization compared to its opponents ZFN and TALEN. A gRNA complementary to the gene sequence that is to be silenced, removed, or replaced is synthesized in the lab and introduced in the host cell. Cas9 opens the host’s DNA helix for its hybridization with gRNA and thereafter slices the target sequence leading to the identification of functions of a particular gene and substitution of mutated/non-functional genes with functional sequences via vectors. The technology has been employed in devising treatments for not only genetic disorders like Sickle-Cell Anemia and Muscular Dystrophy but also, novel coronavirus infection, Cancer, and several other bacterial and viral diseases. It has also been administered in the creation of testing kits for COVID-19 pneumonia infection leading to early diagnosis and reduced dispersal. As the tool can be employed at somatic as well as germline levels, it opens doors to speculation from researchers and ethicists regarding its applications.